Extended supply chain DEA for considering replaceable DMUs - Woramol Chaowarat (2018)
Efficiency evaluation is a critical step for effective supply chain management. The evaluation system should be constructed based on realistic structure of supply chain. In practical supply chain, the members can be divided into two types, replaceable and irreplaceable. However, the current studies do not consider such situations. In order to consider such situation, a two-stage DEA model is going to be extended and proposed. Frozen seafood supply chains of Thailand are presented as an application to show an efficacy and applicability of the proposed model. As a result, eleven inefficient chains have been found by using the proposed model while only six and seven inefficient chains have been found by using traditional models. We can ague that the proposed model can identify an efficiency of the realistic supply chain more sensitively than traditional models. © (2014) Trans Tech Publications, Switzerland.